THE MODEL OF PATIENT SATISFACTION : SERVICE QUALITY, COMMITMENT,ANDDOCTOR’SOCB IN MILITARYHOSPITAL - Widodo, Sri; Yosepha, Sri Yanthy; Satriyanto, Muhammad Dwi; Liana, Esti; Supinganto, Agus; Artama, Syaputra; Fachrial, Peppy; Sidjabat, Sonya (The journal of contemporary issues in business and government, 2021)
This study aims to determine the direct effect of service quality, commitment, and organizational citizenship behavior on patient satisfaction atthe militaryhospital. This research uses quantitative methods and survey methods. Through Slovin, according to the stratified random sampling formula, a total population of 200 patients and a sample of 125 patientswere obtained.Use a Likert scale questionnaireof 1 to 5 for data collection. Analysis equipmentfor path analysis usingExcell and SPSS 25. The results showed: 1) Service quality has a positive and significant direct effect on patient satisfaction of 26.7%; 2) Doctor’s commitmenthas no direct effect on patient satisfaction; 3) Doctor’s organizational citizenship behavior has a positive and significant direct effect on patient satisfaction of 43.3%; 4) Service quality has a positive and significant direct effect on doctor’s organizational citizenship behaviorof 54.7%; 5) Doctor’s commitment has a positive and significant direct effect on doctor’s organizational citizenship behavior of 41.2%, and 6) Service quality has a positive and significant direct effect on doctor’scommitment of 92.1%.